Open data in German municipalities. Between added value and legit concerns? - (:unkn) unknown (Facultas, 2021)
The corona pandemic has shown that open data can have an added value for cities in dealing with the global pandemic. In May 2020, the authors conducted a municipal survey in which officials responsible for data coordination and publication in cities with more than 10,000 inhabitants stated that open data could have an advantage in combating the corona pandemic, for example by informing its citizens and providing local open data to a wider public. Despite these positive assessments, the provision and use of open data in Germany still varies greatly in German municipalities. Against this background, the paper highlights the different perspectives of cities and municipalities on the topic of open data, including: (1) assessments of the opportunities and risks of open data in the municipality, (2) references to the political factors that have favoured or hindered the provision of open data, and (3) desired support for municipalities to conceptualize and implement their own open data strategy. The authors research aims to provide suggestions for and perspectives on why the municipal level in Germany finds it so difficult to implement innovative approaches to data management as part of their digitization efforts.
Keywords: Open Data; Corona-Krise; E-Government; Kommunalverwaltung; Datenmanagement; Verwaltungsdaten; Bürgerinformation; Informationsbereitstellung; Verwaltungshandeln; Digitalisierung; Befragung; Städtevergleich